The KORELASI MOTIVASI BELAJAR TERHADAP KECERDASAN INTELEKTUAL PESERTA DIDIK DI SMA NEGERI 1 MATARAM - Sawaludin; Fitriah Artina; Basariah; I Nengah Agus Tripayana (Unika Santu Paulus Ruteng, 2021)
This study begins with the researcher's assumption that besides facilities and systems effective learning, there are other factors that participate in influencing students of SMAN 1 Mataram to be favorite school to other schools, namely the influence of the internal factors of the students themselves, such as learning motivation of students. Therefore the researcher feels it is necessary to investigate further, to ensure that the achievement or intellectual intelligence of students at SMAN 1 Mataram is built from within the students' personal. This study uses quantitative research with a non-experimental approach. The population was students of SMAN 1 Mataram, the sample was taken using random class. Data analysis uses the product moment correlation statistical formula. The results obtained by the relation of variables between students' learning motivation (X) with intellectual intelligence of students (Y) obtained by Fcount of 17.41 with Ftable of 3.34 at a confidence level of 0.05, it can be said that there is a significant relations where Fcount > Ftable. In other words the alternative hypothesis (Ha) is accepted and (Ho) is rejected. This can be explained that in addition to facilities and adequate learning environment conditions, students of SMAN 1 Mataram have a good level of motivation, so that it can affect the intellectual intelligence of students who study in the environment.